EKSTRAK KEMANGI (OCIMUM BASILICUM L) YANG BERBEDA DAN PENGARUHNYA TERHADAP FISIKOKIMIA DAN ORGANOLEPTIK DENDENG SAPI (Jurnal Peternakan Nusantara, 2022)
This study aims to obtain the best concentration of basil extract as an ingredient for making beef jerky by analyzing the water content, pH, antioxidant and organoleptic content of beef jerky. This study used a completely randomized design, namely soaking meat with different concentrations of basil. The use of basil has three levels of immersion concentration, namely P1 = 20%, P2 = 25%, P3 = 30%, P4 = 35%. The need for soaking meat with basil is 20 sample units. The variables measured were water content, pH, antioxidants, and organoleptic including color, taste, texture and preference. Parameter testing is first tested for normality by using the Shapiro-Wilk test. If the data distribution is normal, then the ANOVA is at the 5% level, if there is an effect, it is continued with the Duncan Multiple Region test. Antioxidants were tested descriptively and organoleptic properties (color, taste, texture and preference) were tested using the Kruskal-Walis Non Parametric test and continued, the Man Witney significant difference test. The results of this study indicate that different concentrations of basil can have a significant effect (P <0.05) on water content, pH and organoleptic. The higher concentration of basil extract can reduce the water content, normalize the pH value, improve organoleptic. Giving basil concentration 25% to 35% can increase antioxidant activity.